Sexual attitudes of personnel who work with individuals with intellectual disability [Postoje personálu pracujícího s osobami s mentálním postižením vůči sexualitě] - Jana Divišová-Brettová; Dana Štěrbová (Palacky University, 2009)
The capacity, in the Czech Republic, for measuring attitudes towards this important aspect of a person's life is limited by the lack of an appropriate instrument. The aim of this study was to adapt the new instrument "Attitudes to Sexuality Questionnaire" (Cuskelly & Gilmore, 2007) and translate it into the Czech language. The purpose of this study was to examine, in the pilot study, the attitudes of schoolmasters toward the sexuality of persons with intellectual disability. From among Special Olympics participants, 20 persons (n = 20, 11 females and 9 males) were enrolled in this study. From the results it is apparent that respondents held positive attitudes toward people with intellectual disability and toward people from the general population. The most positive views were toward the non reproductive sexual behaviour subscale. The less positive views were presented toward the sexual rights subscale. A review of the literature contained a comparison of the situation in social systems providing services for people with intellectual disability in Australia and the Czech Republic and the development of the attitudes toward the sexuality of people with intellectual disability. [Česká republika bohužel disponuje malým počtem vhodných instrumentů k měření postojů vůči sexualitě - tomuto důležitému aspektu lidského života. Cílem této práce bylo adaptovat nový instrument "Dotazník o postojích vůči sexualitě" (Cuskelly & Gilmore, 2007) a přeložit jej do češtiny. Tento dotazník je původem z Austrálie a autorka Monica Cuskelly písemně souhlasila s přeložením a používáním jejího dotazníku v České republice. Dalším cílem této práce byla v pilotní studii evaluace postojů vychovatelů vůči sexualitě osob s mentálním postižením a vůči sexualitě osob z běžné populace. Zůčastnilo se 20 osob (11 žen a 9 mužů), které byly vybrány na speciální olympiádě. Z výsledků je zřejmé, že účastníci disponují pozitivními postoji vůči sexualitě osob s mentálním postižením a také vůči sexualitě osob z běžné populace. Přehled literatury obsahuje srovnání českého a australského sociálního systému poskytujícího služby osobám s mentálním postižením a vývoj postojů vůči sexualitě osob s mentálním postižením.]